4x(x-y)-(2x-3y)(2x-3y) x=1 y=-1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 09:14:03
4x(x-y)-(2x-3y)(2x-3y)x=1y=-14x(x-y)-(2x-3y)(2x-3y)x=1y=-14x(x-y)-(2x-3y)(2x-3y)x=1y=-14x(x-y)-(2x-3
4x(x-y)-(2x-3y)(2x-3y) x=1 y=-1
4x(x-y)-(2x-3y)(2x-3y) x=1 y=-1
4x(x-y)-(2x-3y)(2x-3y) x=1 y=-1
4x(x-y)-(2x-3y)(2x-3y)
=4x^2-4xy-4x^2-9y^2+12xy
=8xy-9y^2
=8*1*(-1)-9(-1)^2
=-8-9
=-17
4x(x-y)-(2x-3y)(2x-3y)其中 x=1 ,y=-1
解,得:
==4x(x-y)-(2x-3y)^2
==8-25
==-17
x(x-y)2-(y-x)3
[2/3x-2/x+y(x+y/3x-x-y)]/x-y/x
化简:{2/3x-2/(x+y)[(x+y)/3x-x-y]}/(x+y)/x
计算2/3x-2/x+y(x+y/3x-x-y)/x-y/x
化简3x-2/(x+y)[(x+y)/3x-x-y]÷(x-y)/x
(x-y) (x-2y)+(x+2y) (x-3y)-2(x-3y) (x-4y)=
x²/xy-x/y 3x/4x+y - x-2y/4x+y (1-y/y+x)÷x/y²-x²
(x+3y-4)(2x-y)
计算(2x-3y)(x+4y)-(3x+y)(x-2y)(2x-3y)(x+4y)-(3x+y)(x-2y)
因式分解(x-2y)(x-3y)+(x-4y)(x-5y)+(x-3y)(x-5y)+(x-2y)(x-4y)
(2x+y)(2x-3y)+x(2y+y) 2a(x-y)-4b(x-y)
[(3x+y)(x-y)-(2x+3y)(x-y)]*(x-y)
计算:x+2y/x-y+2x/y-x-3y/x-y
化简:(x-3y)(x+y)-(x-2y)(x+2y)-(x-y)平方
(2x-y)(2x+y)-2(3x-4y)(4y+3x)
(3x-y)(y+3x)-2(4x-3y)(4x+3y)
化简:2x-{-3y+[4x-(3x-y]}
x^3+2x^2y-4x-8y